Towards an evidence-based regulation of cybercrime - Lara, Juan Carlos; Martínez, Manuel; Viollier, Pablo (Revista Chilena de Derecho y Tecnología, 2014)
The Chilean legal system has faced the problem of digital criminal behavior in an inconsistent way. It has imposed punishment to certain conducts necessarily associated with the presence of technologies in a reactive and disintegrated manner. Furthermore, it has set aside the consideration of technological tools in the commission of traditional crimes, specifically devoting their use as a method for committing crimes in specific hypotheses. While national scholars have attempted to systematize the national regulation, the legislation still has inconsistencies that sometimes have resulted in the use of rules to punish acts where the attacked and the protected objects of the rule are different. The potential adhesion to treaties on the subject, and the possible renewal of the Chilean Penal Code, are opportunities to reform the system. This paper attempts to determine the suitability of the act 19.223 on cybercrime from statistical evidence, in order to enrich the discussion on a new regulation of this criminal phenomenon.